Optimizing Tiktok For Enhancing Brand Awareness In MSMEs: A Case Study of Kopi Toko Tua - Najwa, Savira; Cahyani, Leni (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study investigates the strategic use of TikTok to enhance brand awareness at the MSME Kopi Toko Tua, focusing on its role in engaging Gen Z consumers and strengthening brand identity. Methodology: This research adopts a qualitative case study approach using in-depth interviews, field observations, and documentation involving the business owner, marketing team, and selected customers. The collected data were analyzed using Miles and Huberman’s interactive model. Results: The results indicate that storytelling-based content, vintage–modern visual aesthetics, and soft-selling communication strategies effectively increase audience engagement and foster emotional connections with the brand. However, inconsistent posting schedules and limited utilization of TikTok’s interactive features were identified as key challenges limiting optimal performance. Novelty: This study highlights TikTok as a lifestyle-driven branding platform rather than merely a promotional tool for MSMEs. Findings: Audience segmentation, lifestyle-oriented narratives, and responsiveness to trending content are critical in shaping positive consumer perceptions and encouraging offline purchase decisions. Originality: The originality of this study lies in its focus on TikTok-based narrative branding within a local MSME context, which remains underexplored in prior social media marketing studies. Conclusions: Strategic and consistent use of TikTok content can significantly enhance brand awareness and consumer engagement for MSMEs. Type of Paper: Qualitative Case Study.